Model of fracture micro mechanism of Cu-Cr-Zr system by in-situ tensile test in SEM - Besterci M.; Ivan J.; Kulu P.; Arensburger D.; Velgosova O. (Journal of Mining and Metallurgy. Section B: Metallurgy)
In the present work fracture mechanism of the Cu-Cr-Zr system was studied by "in-situ tensile test in SEM". It has been shown, that during tensile strain over the critical deformation the first cracks appeared due to the decohesion of matrix - large Cr particles interphase or by Cr particles failure. The further stress increase causes the cracks formation on matrix small Cr particles interfaces and in the clusters of Cu5Zr intermetalics. The trajectory affinal fracture was formed preferably by coalescence of cracks oriented about 67° to the loading direction. The model, presenting fracture mechanism in the investigated system was suggested.